Deixis In Taglines: A Socio-Cultural Semiotic Analysis - Siti Nurani; Nico Harared (Scope : Journal of English Language Teaching, 2017)
The research aims at analyzing the socio-cultural semiotic that characterize the deixis in taglines. Such types of deixis are analyzed qualitatively by examining the socio-cultural functions using “Sign Mapping of Roland Barthes”. The analysis focuses in describing the signifier and signified as well as the meaning of denotative and connotative characterized the deixis in taglines of various advertisements. Findings have shown that the signifiers and signified concepts function to inform, to challenge, to emphasize, and to persuade, of the consumers as the addressee. The types of deixis occur into such types of pronominals deixis (she, you, I, me), nominal deixis (girl, age, the city), verbal (blow, drive, come, follow, let, change), adverbial (in her face, anywhere, Marlboro country, when you can fly), and grammatical deixis (imperative, statement, interrogative). The denotative meaning is reflected from the use of signifiers that serves the real of sense of the product referred to, i.e., the commercial product that is divided into categories, man’s category, woman’s category, and unmarked category. The connotative meaning relates to some cultural values, such as pleasure, masculinity, feminity, passion, luck, beauty, freedom, and the sense of belonging.Key words: Socio-cultural semiotic analysis, deixis, tagline